2014
DOI: 10.1371/journal.pone.0087354
|View full text |Cite
|
Sign up to set email alerts
|

β-Hairpin-Mediated Formation of Structurally Distinct Multimers of Neurotoxic Prion Peptides

Abstract: Protein misfolding disorders are associated with conformational changes in specific proteins, leading to the formation of potentially neurotoxic amyloid fibrils. During pathogenesis of prion disease, the prion protein misfolds into β-sheet rich, protease-resistant isoforms. A key, hydrophobic domain within the prion protein, comprising residues 109–122, recapitulates many properties of the full protein, such as helix-to-sheet structural transition, formation of fibrils and cytotoxicity of the misfolded isoform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 105 publications
2
14
0
Order By: Relevance
“…Our extensive REMD simulations show that the monomeric A117V mutated PrP106-126 exhibits the higher contents of β-hairpin in contrast with its wild type, consistent with the results of Monte Carlo simulations [ 22 ]. The CD spectroscopy experiments suggested that the A117V mutation increased β-sheet structure[ 30 ].…”
Section: Resultssupporting
confidence: 85%
“…Our extensive REMD simulations show that the monomeric A117V mutated PrP106-126 exhibits the higher contents of β-hairpin in contrast with its wild type, consistent with the results of Monte Carlo simulations [ 22 ]. The CD spectroscopy experiments suggested that the A117V mutation increased β-sheet structure[ 30 ].…”
Section: Resultssupporting
confidence: 85%
“…They looked similar to the disaggregation of amyloid fibrils by capreomycin (Siddiqi et al, 2018). The mesh of fibers in peptide P3 incubated with HNQ disappeared ( Figure 1B) as has been observed in similar studies on inhibitor action of 1,4-naphthoquinones (Gill, 2014), quinones (Gong et al, 2014), and other polyphenols (Ono et al, 2003), and copper (Mold et al, 2013) on amyloid formations. Amyloid β treated with white tea also showed amorphous aggregates whereas the overall density of aggregates was less in those samples treated with other types of tea (Li et al, 2019).…”
Section: Inhibitory Action Of Hnqsupporting
confidence: 83%
“…These data suggest that hairpin‐like structures could be crucial in the assembly of other polyQ diseases as well. A molecular dynamics simulation study with the amyloidogenic fragments of murine Prion protein, PrP 109‐122 , PrP 106‐126 , and their Ala117Val mutants suggests that the assembly is mediated by β‐hairpin structures . Even though AβWW is not amyloidogenic, AβWW β‐turn analogs cause ~7‐10‐fold enhancement in ThT fluorescence intensity.…”
Section: Discussionmentioning
confidence: 99%
“…A molecular dynamics simulation study with the amyloidogenic fragments of murine Prion protein, PrP 109-122 , PrP 106-126 , and their Ala117Val mutants suggests that the assembly is mediated by β-hairpin structures. [47] Even though AβWW is not amyloidogenic, AβWW β-turn analogs cause~7-10- The structure of Aβ 14-23 fibrils has been investigated using solid-state NMR. [48] The fibrils are made up of antiparallel β-sheets with a registry that aligns residue 17+k with residue 22-k, where k is an integer.…”
Section: Discussionmentioning
confidence: 99%